2003
DOI: 10.1258/026835503322381324
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer compression: comparison of four different four-layer bandage systems applied to the leg

Abstract: Objective: To compare on standardized laboratory models the performance of four commercially available four-layer bandage systems. Methods: Four experienced bandagers applied each of the four systems [Profore® Regular (Smith & Nephew, Hull, UK), Ultra Four (Robinsons, Chesterfield, UK), System 4 (SSL International, Knutsford, UK) and K-Four® (Parema, Loughborough, UK)] to two models: a 12.5 cm diameter padded cylinder and a 9.5-14.5 cm padded cone. Bandages were applied individually in single layers and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The DLC is composed of 3 layers, but the inner cotton layer functions to pad the limb from the pressure of the outer layers. Human literature demonstrates that adding more than 2 compressive layers offers limited benefit to the cumulative sub‐bandage pressure . Dale et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DLC is composed of 3 layers, but the inner cotton layer functions to pad the limb from the pressure of the outer layers. Human literature demonstrates that adding more than 2 compressive layers offers limited benefit to the cumulative sub‐bandage pressure . Dale et al .…”
Section: Discussionmentioning
confidence: 99%
“…The DLC is composed of 3 layers, but the inner cotton layer functions to pad the limb from the pressure of the outer layers. Human literature demonstrates that adding more than 2 compressive layers offers limited benefit to the cumulative sub-bandage pressure [19]. Dale et al [20] demonstrated that when an additional compressive layer is applied to a multilayer bandage construct, it applies only 50-60% of the pressure exerted when applied individually.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers conducting studies in man concluded that applying additional compressive layers did not have a purely additive effect, but a decrease in sub‐bandage pressure has not been reported . Ruckley et al and Dale et al demonstrated that an additional compressive layer in a multilayer bandage construct creates only 50%‐75% of the pressure exerted when applied individually . With regard to the DL, the addition of the second CombiRoll and brown gauze layer further separates the elastic layer from the bandage–skin interface.…”
Section: Discussionmentioning
confidence: 99%
“…8 Ruckley et al 8 and Dale et al 9 demonstrated that an additional compressive layer in a multilayer bandage construct creates only 50%-75% of the pressure exerted when applied individually. 8,9 With regard to the DL, the addition of the second CombiRoll and brown gauze layer further separates the elastic layer from the bandage-skin interface. In DL, we speculate that the pressure applied by the elastic layer compresses both Combi rolls, dissipating the pressure within the bandage construct and reducing the pressure applied to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…11 Next we analysed data when four commercially available four-layer bandaging systems were applied on models. 12 We now compare the same bandaging systems when applied on the leg.…”
Section: Introductionmentioning
confidence: 99%